300,000+ African farmers overcome banana Xanthomonas wilt using Alliance-developed single diseased stem removal with other measures. - Blomme, Guy; Ocimati, Walter; Kikulwe, Enoch; Johnson, Vincent (2025)
An Alliance partnership has finalized a bundle of highly effective, low-cost, and user-friendly banana Xanthomonas wilt disease (BXW) control technologies including Single Diseased Stem Removal (SDSR), to protect East and Central Africa’s multibillion dollar banana production and >3 million farmers’ livelihoods across the region [1]. SDSR has been adopted by > 300,000 banana farmers on >100,000 ha of bananas in Burundi, eastern DR Congo, Rwanda, Tanzania, and Uganda, providing 96% recovery in control costs and reducing BXW incidence to below 1% within 10 months, compared to traditional methods [2,3,4,5].